Total pelvic exenteration for rectal cancer: outcomes and prognostic factors - Domes, Trustin S. (Canadian Medical Association, 2011)
BACKGROUND: To perform complete resection of locally advanced and recurrent rectal carcinoma, total pelvic exenteration (TPE) may be attempted. We identified disease-related outcomes and prognostic factors. METHODS: We conducted a single-centre review of patients who underwent TPE for rectal carcinoma over a 10-year period. RESULTS: We included 28 patients in our study. After a median follow-up of 35 months, 53.6% of patients were alive with no evidence of disease. The 3-year actuarial disease-free and overall survival rates were 52.2% and 75.1%, respectively. On univariate analysis, recurrent disease, preoperative body mass index greater than 30 and lymphatic invasion were poor prognostic factors for disease-free survival, and only lymphatic invasion predicted overall survival. Additionally, multivariate analysis identified lymphatic invasion as an independent poor prognostic factor for disease-free survival in this patient population with locally advanced and recurrent rectal carcinoma. CONCLUSION: Despite the significant morbidity, TPE can provide long-term survival in patients with rectal carcinoma. Additionally, lymphatic invasion on final pathology was an independent prognostic factor for disease-free survival.